Use of Halfa Bar Essential Oil (HBO) as a Natural Growth Promoter in Broiler Nutrition - Amal, O.A.; Mukhtar , A.M.; Mohamed, K.A.; Ahlam, A.H. (International Journal of Poultry Science, 2012)
This experiment was conducted to evaluate the response of broiler chicks to diets containing graded levels of essential oil extracted from Halfa Bar Oil (HBO). A total of 160, five days-old, unsexes (Ross 308) broiler chicks were used. Chicks were weighed individually and assigned randomly to five groups of 32 chicks per treatment and each treatment group consisted of four replicates of 8 chicks per each. Five experimental diets were formulated (A, B, C, D and E) to meet the nutrient requirements. The experimental parameters covered growth performance, carcass characteristics serum metabolite, electrolyte and enzyme activities. Diets A as Negative Control (NC), diet B control diet supplemented with antibiotic (Neomycin 16 mg/Kg) as Positive Control (PC), diets C, D and E were NC supplemented with Halfa Bar Oil (HBO) at 50, 100 and 150 mg/Kg, respectively. Result obtained showed that addition of HBO improved significantly (P